Adaptation and validation of the Patient Expectations and Satisfaction with Prenatal Care instrument among Brazilian pregnant women Adaptación y validación del Patient Expectations and Satisfaction with Prenatal Care para embarazadas brasileñas Adaptação e validação do Patient Expectations and Satisfaction with Prenatal Care para gestantes brasileiras - Patrícia Santos Prudêncio; Fabiana Villela Mamede; Rosana Aparecida Spadoti Dantas; Luiz de Souza; Marli Villela Mamede (Universidade de São Paulo, 2013)
OBJECTIVE: to adapt and validate the Patient Expectations and Satisfaction with Prenatal Care instrument for use in Brazil. It contains 41 items divided into two dimensions: expectations and satisfaction. The adapted version was submitted to analysis for stability, convergent construct validity, and internal consistency (Cronbach's alpha) for distinct groups and dimensions. METHOD: 119 pregnant women receiving prenatal care were interviewed and 26 of these women answered the instrument twice (retest). Internal consistency was appropriate (Cronbach's alpha ≥ 0.70); test-retest presented strong correlation (r=0.82; p<0.001) for the domain expectations and moderate correlation (r=0.66; p<0.001) for the satisfaction domain. The analysis confirmed that the instrument's adapted version is valid in the studied group. RESULTS: there is strong evidence for the validity and reliability of the instrument's adaptation. CONCLUSION: the instrument needs to be tested in groups of pregnant women with different social characteristics. OBJETIVO: adaptar para uso en Brasil y validar el instrumento Patient Expectations and Satisfaction with Prenatal Care que contiene 41 ítems, divididos en dos dominios (expectativa y satisfacción). La versión adaptada fue sometida al análisis de validez de constructo convergente, de grupos distintos y dimensionalidad y de la consistencia interna (alfa de Cronbach) y estabilidad. MÉTODO: fueron entrevistadas 119 embarazadas en acompañamiento prenatal, de esas 26 respondieron dos veces el instrumento (reprueba). La consistencia interna fue adecuada (Alfa de Cronbach ≥ 0,70) y la prueba-reprueba presentó correlación fuerte (r=0,82; p<0,001) para la expectativa y correlación moderada (r=0,66; p<0,001) para la satisfacción. Los análisis realizados confirmaron la validez de la versión adaptada del instrumento en el grupo estudiado. RESULTADOS: indicaron fuertes evidencias de validez y confiabilidad de la versión adaptada del instrumento. CONCLUSÍON: el instrumento necesita ser comprobado en grupos de embarazadas con diferentes características sociales. OBJETIVO: adaptar para uso no Brasil e validar o instrumento Patient Expectations and Satisfaction with Prenatal Care, que contém 41 itens, divididos em dois domínios (expectativa e satisfação). A versão adaptada foi submetida à análise da validade de constructo convergente, de grupos distintos, e dimensionalidade, além da análise da consistência interna (alfa de Cronbach) e estabilidade. MÉTODO: foram entrevistadas 119 gestantes em acompanhamento pré-natal; dessas, 26 responderam duas vezes ao instrumento (reteste). A consistência interna foi adequada (alfa de Cronbach ≥ 0,70) e o teste/reteste apresentou correlação forte (r=0,82; p<0,001) para a expectativa e correlação moderada (r=0,66; p<0,001) para a satisfação. As análises realizadas confirmaram a validade da versão adaptada do instrumento no grupo estudado. RESULTADOS: os resultados indicaram fortes evidências de validade e confiabilidade da versão adaptada do instrumento. CONCLUSÃO: o instrumento necessita ser testado em grupos de gestantes com diferentes características sociais.